THE DEVELOPMENT OF PRODUCT PACKAGING IN AN EFFORT TO INCREASE PUBLIC INTEREST IN TRADITIONAL FOOD BARUASA IN GAYA BARU VILLAGE, TELLU LIMPOE DISTRICT, BONE REGENCY - Fatimah Zahra; Agus Syam; Asmayanti (BORJUIS: JURNAL OF ECONOMY, 2024)
This research aims to modify the packaging of the Baruasa product, with the hope of increasing public purchasing interest. The development method used is the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. (Evaluasi). The analysis stage involves assessing consumer needs, the design stage includes creating packaging that aligns with the findings from the needs analysis. The prototype of the packaging is developed during the development stage, and implementation is carried out by showcasing the new packaging to consumers. Evaluation is conducted to assess the effectiveness of the packaging based on consumer responses. The research results show that the packaging of the Baruasa product is very suitable, with a percentage of 84.7%. Consumer responses from the survey indicate that the packaging of the Baruasa product is highly appropriate. It can be concluded that good product packaging can enhance public interest in traditional Baruasa food.